2017
DOI: 10.3390/cryst7060174
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in Time of Radiation Defects Induced by Negative Pions and Muons in Crystals with a Diamond Structure

Abstract: Evolution in time of radiation defects induced by negatively-charged pions and muons in crystals with diamond structures is considered. Negative pions and muons are captured by the nucleus and ionize an appropriate host atom, forming a positively-charged radiation defect in a lattice. As a result of an evolution in time, this radiation defect transforms into the acceptor center. An analysis of the full evolution process is considered for the first time. Formation of this acceptor center can be divided into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Calculations of a radiation transition rate of the neutral defect in the chemically bound state in the "main" crystals with a diamondtype structure (C, Si and Ge) in the assumption of a fast neutralization, were carried out in [21]. However, in accordance with conclusions in [22], the obtained results appear to be correct only for silicon and germanium, while for diamond it is necessary to consider the formation process of a chemically bound positively charged defect.…”
Section: States Of the ( μ B) + Center In A Latticesupporting
confidence: 57%
See 3 more Smart Citations
“…Calculations of a radiation transition rate of the neutral defect in the chemically bound state in the "main" crystals with a diamondtype structure (C, Si and Ge) in the assumption of a fast neutralization, were carried out in [21]. However, in accordance with conclusions in [22], the obtained results appear to be correct only for silicon and germanium, while for diamond it is necessary to consider the formation process of a chemically bound positively charged defect.…”
Section: States Of the ( μ B) + Center In A Latticesupporting
confidence: 57%
“…To confirm the suggestion on a fast neutralization of a radiation defect, calculations of electron capture by a charged radiation defect, formed by a negative muon in silicon and diamond crystals [21,22], were performed. The calculations in [22] have shown that the kinetics of electron capture by a positively charged radiation defect in silicon and diamond is essentially different.…”
Section: States Of the ( μ B) + Center In A Latticementioning
confidence: 93%
See 2 more Smart Citations
“…In addition, this question is also important for the process of ion implantation, which is frequently used to modify diamond properties [60]. Yury Belousov in his contribution reports in-depth theoretical calculations of the time evolution of radiation defects induced by negative pions and muons in diamond, silicon, and germanium [61]. Radiation damage of diamond by these particles is not commonly considered, but since they are the products of the interaction of high-energy protons with a target, the corresponding radiation defects may be important for the relevant applications.…”
Section: Some Facets Of Synthetic Diamond Crystalsmentioning
confidence: 99%